Case report: Preliminary experience with organ-preserving treatment for locally advanced esophageal cancer in the immunotherapy era: a case series of four patients - Yang, Genrong; Wang, Han (Frontiers in Oncology, 2025)
BackgroundFor resectable locally advanced esophageal cancer, a comprehensive treatment strategy primarily centered on surgery is commonly adopted in clinical practice. Although the minimally invasive approach has reduced surgical trauma, the altered postoperative physiological structure often leads to impaired digestive function, reflux, and malnutrition, which significantly impact patients’ quality of life. With the incorporation of immune checkpoint inhibitors, some patients achieve a pathological complete response(pCR) after neoadjuvant therapy. As a result, these patients may become ideal candidates for organ-preservation strategies.Case presentationA retrospective analysis was conducted on four patients with locally advanced esophageal cancer who received chemoimmunotherapy with selective radiotherapy. Pathological response and recurrence-free survival (RFS) were assessed. All four patients achieved complete pathological response. Cases 1, 2, and 3 were followed for 42 months, 31 months, and 25 months, respectively, with no recurrence. Case 4 experienced recurrence after 18 months of follow-up. Reinitiated chemoimmunotherapy was ineffective, and the tumor showed slow progression on subsequent lines of therapy.ConclusionChemoimmunotherapy with selective radiotherapy may offer an organ-preserving opportunity for locally advanced esophageal cancer, with some patients achieving long-term recurrence-free survival. However, efficacy varies individually, and further optimization of treatment strategies is warranted.